Biofluid Mechanics : The Human Circulation - Chandran, K. B.; Rittgers, Stanley E., Yoganathan, A. P. (Boca Raton : CRC Press, Taylor & Francis Group, 2012)
"Examining the biodynamics of heart disease, this updated edition reviews the fluid mechanical analysis of blood flow in the human arterial circulation. It focuses on the development and progression of the disease as well as the tools and technology at the cutting edge of treatment. Applying the theory of fluid mechanical principles in human circulation, the text evaluates the design and development of circulatory implants, such as artificial heart valves, ventricular assist devices, and vascular grafts. This edition includes a new chapter on simulations, along with new illustrations, problems, and examples"--
Revision of: Biofluid mechanics / Krishnan B. Chandran, Ajit P. Yoganathan, Stanley E. Rittgers. 2007.
Keywords: Blood Circulation -- physiology; Cardiovascular Physiological Phenomena; Heart Valves -- physiology